Severe asthma in obese patients: Improvement of lung function after treatment with omalizumab - M.J. Oliveira (Pulmonology, 2019)
Introduction: Asthma and obesity have a considerable impact on public health and their prevalence is increasing. Obesity is a known risk factor for asthma and can make it more difficult to control. Omalizumab is recommended in patients with severe allergic persistent asthma. The aim of this study was to assess the impact of omalizumab treatment in obese asthmatic patients with poorly controlled severe persistent asthma. Methodology: A non-interventional, prospective study was conducted, in an outpatient asthma clinic. All patients with severe asthma who started treatment with omalizumab were included and followed over 12 months. The study population was divided into two groups (obese and non-obese) for statistical analysis (descriptive and comparative analysis). Results: Thirty-two patients (19 obese) were followed. After 12 months of omalizumab treatment, there was a statistically significant improvement in body mass index, number of exacerbations in the previous year, rescue medication, disease control and lung function, in the whole population. At the end of the study obese patients had a significantly better lung function (FEV1) than non-obese. Discussion: As described in the literature, there was a significant reduction in the number of exacerbations in the previous year, rescue medication and better disease control, in the whole population. In relation to lung function, about which published data are inconsistent, treatment with omalizumab significantly improved it in obese patients. Conclusion: Our study showed that omalizumab significantly improved asthma control, reduced rescue medication and asthma exacerbations in all the population; and for the first time showed that obese patients achieved significantly improved lung function. Keywords: Asthma, Severe asthma, Lung function, Omalizumab